Prolonged infusion of β-lactams decreases mortality in patients with septic shock: a retrospective before-and-after study - Richter, Daniel; Dietrich, Maximilian; Lalev, Lazar Detelinov; Schmitt, Felix; Fiedler-Kalenka, Mascha; Bruckner, Thomas; Störzinger, Dominic; Chiriac, Ute; Klein, Sabrina; Hackert, Thilo; Brenner, Thorsten; Brinkmann, Alexander; et al. (Antibiotics, 2021)
Septic shock substantially alters the pharmacokinetic properties of β-lactams with a subsequently high risk of insufficiently low serum concentrations and treatment failure. Considering their pharmacokinetic (PK)/pharmacodynamic (PD) index, prolonged infusions (PI) of β-lactams extend the time that the unbound fraction of the drug remains above the minimal inhibitory concentration MIC (ft >MIC) and may improve patient survival. The present study is a monocentric, retrospective before-and-after analysis of septic shock patients treated with β-lactams. Patients of the years 2015-2017 received intermittent bolus application whereas patients of 2017-2020 received PI of β-lactams. The primary outcome was mortality at day 30 and 90 after diagnosis of septic shock. Mortality rates in the PI group were significantly lower on day 30 (PI: 41%, n = 119/290 vs. IB: 54.8%, n = 68/114; p = 0.0097) and day 90 (PI: 47.9%, n = 139/290 vs. IB: 62.9%, n = 78/124; p = 0.005). After propensity-score matching, 30- and 90-day mortality remained lower for the PI group (−10%, p = 0.14). PI was further associated with a reduction in the duration of invasive ventilation and a stronger decrease in SOFA scores within a 14 day-observation period. PI of β-lactams was associated with a significant reduction of mortality in patients with septic shock and may have beneficial effects on invasive ventilation and recovery from sepsis-related organ failure.
Gesehen am 05.08.2021